What’s the importance of portable tele-monitoring devices in patient therapeutic adherence? - Rodrigues, Orlando (2017)
In the UK it is estimated the NHS spends almost £100 million every year in unused drugs. In addition, hospital admission costs attributed to patients not taking their prescribed medicine properly was estimated to be between £36m and £197m per year. In the U.S., medication non-adherence is estimated to lead to between $100 and $300 billion of avoidable healthcare costs annually, representing 3–10% of total U.S. healthcare costs. Studies show that improving medication adherence may have a greater influence on the health of the population than the discovery of any new therapy. Effective medicines are available for many conditions and yet patients are non-adherent 50% of the time. This can be critical point in certain disease states, such as asymptomatic conditions like hypertension, where the incidence may approach 80% non-compliance. It is proposed to create a therapeutic adherence monitoring device within a smart blister pack that is coupled to a device with the capacity to collect and send data to a common server. This would allow a clinician to know, with high certainty, if the patient is taking their medication as prescribed and on schedule. This paper gathers information to identify current technology to support integrated monitoring and control of therapeutic adherence.